Dictyota and Canistrocarpus Brazilian Brown Algae and Their Bioactive Diterpenes—A Review - Ana Débora Nunes Pinheiro Georgii; Valéria Laneuville Teixeira (Marine Drugs, 2023)
Dictyotaceae algae have gained recognition as prolific producers of diterpenes, which are molecules with significant biotechnological potential. These diterpenes hold immense promise as potential active drug components, making the algae a compelling area of study. The present review aims to present the latest advancements in understanding the biopotential of Brazilian Dictyota and Canistrocarpus brown algae, shedding light on the remarkable diversity and the biological and pharmacological potential of the secondary metabolites they produce. A total of 78 articles featuring 26 distinct diterpenes are reported in this review, with their antiviral potential being the most highlighted biological activity. Despite considerable research on these algae and their diterpenes, significant knowledge gaps persist. Consequently, the present review is poised to serve as a pivotal resource for researchers who are actively engaged in the pursuit of active diterpenes beyond the immediate purview. Furthermore, it holds the potential to catalyze an increase in research endeavors centered around these algal species within the geographical confines of the Brazilian coastline. Also, it assumes a critical role in directing future scientific explorations toward a better comprehension of these compounds and their ecological implications.